The Blake book - Myrone, Martin (Tate Pub., 2007)
'The Blake Book' provides a thorough introduction to the life and work of William Blake, and draws on the vast array of contemporary scholarship, providing a clear-headed overview of Blake's writings and paintings.
Includes bibliographical references (p. 217-218) and index
Keywords: Blake, William -- 1757-1827 -- Criticism and interpretation; Blake, William -- 1757-1827; Bildband